Perspectives on Swedish Regulations for Online Record Access Among Adolescents With Serious Health Issues and Their Parents: Mixed Methods Study - Hagström, Josefin; Blease, Charlotte; Harila, Arja; Lähteenmäki, Päivi; Scandurra, Isabella; Hägglund, Maria (JMIR Publications Inc., 2025)
Background: With the increasing implementation of patient online record access (ORA), various approaches to access to minors’ electronic health records have been adopted globally. In Sweden, the current regulatory framework restricts ORA for minors and their guardians when the minor is aged between 13 and 15 years. Families of adolescents with complex health care needs often desire health information to manage their child’s care and involve them in their care. However, the perspectives of adolescents with serious health issues and their parents have not been studied.
Objective: This study aims to qualitatively and quantitatively investigate the perceived benefits and risks of ORA and the awareness of and views on ORA regulations among adolescents with serious health issues and their parents in Sweden.
Methods: We used a convergent mixed methods (qualitative and quantitative) design, consisting of a survey and semistructured individual interviews with adolescents with serious health issues (aged 13-18 y) and their parents. Participants were recruited via social media and in clinics. Quantitative data were presented descriptively. Interviews were audio recorded, transcribed, and analyzed using inductive thematic content analysis.
Results: The survey population included 88 individuals (adolescents: n=31, 35%; parents: n=57, 65%). Interviews were completed by 8 (26%) of the 31 adolescents and 17 (30%) of the 57 parents. The mean age of the surveyed adolescents was 16 (SD 1.458) years, and most of the parents (29/57, 51%) were aged 45 to 54 years. The surveys indicated that most of the parents (51/56, 91%) were critical of the access gap, and most of the adolescents (20/31, 65%) were unaware of the age at which they could gain access. In the interviews, adolescents and parents identified benefits related to ORA that were categorized into 6 themes (empowering adolescents, improved emotional state, enhanced documentation accuracy, improved partnership and communication, supported parental care management, and better prepared for appointments) and risks related to ORA that were categorized into 4 themes (emotional distress and confusion, threatened confidentiality, increased burden, and low usability). Adolescents’ and parents’ views on ORA regulations were categorized into 3 themes (challenges of the access gap, balancing respect for autonomy and support, and suggested regulatory change).
Conclusions: In Sweden, ORA regulations and a lack of available information cause significant inconvenience for adolescents with serious health issues and their parents. Views on access age limits differed, with adolescents expressing their perceived need for independent access, while parents exhibited concerns about adolescents having ORA. The findings indicated the importance of increased education, dialogue, and flexibility to uphold confidential and consistent delivery of adolescent health care. Further exploration is needed to understand the experiences of adolescents and parents in diverse clinical and geographic contexts, as well as the perspectives of pediatric health care professionals on restrictive ORA regulations